PENGOLAHAN SAMPAH ORGANIK MENJADI KOMPOS UNTUK MENDUKUNG KAMPUNG PRO IKLIM - Normela Rachmawati; Susilawati Susilawati; Eva Prihatiningtyas (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2019)
Trash  is  a  major problem in  Banjarbaru City thus far.    The  trash volume in  Banjarbaru approximately 120 tons per day on year 2017-2018 and that goes to landfill thereabouts 105 tons. Therefore,  it is important manage the household waste, so do on  community level through "Bank of  Trash"  as  an  efforts in  creating a  Pro  Climate  (PROKLlM) hometown. Household waste management success through Bank of Trash as one of the efforts of creating "Kampung Proklim" is influenced by the level of knowledge and skill of group manager, waste management technology that mastered, management of waste,  community support and the participation of other institutions.  The  General conditions of  the  Bank Trash  Benawa Raya Mandiri (BRM) is quite adequate, but merely collecting and  selling inorganic garbage from citizens around settlement of Benawa Raya Mandiri to the  Gatherer, on the other hand, organic waste is available in abundance in settlement area  of  Benawa Raya Mandiri, so it consider to be necessary to open such group counselling and training to transfer knowledge and technology to process the organic waste become compost.Keywords: Bank of Trash, Pro Climate Hometown , Compost